Pengaruh motivasi, pelatihan dan job analisis terhadap kinerja karyawan PT. Warni Indah Cemerlang - Lityaui '; Machasin '; Restu Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine the influence of motivation, training and job analysis to employee performance of PT. Warni Indah Cemerlang Pekanbaru. This research use motivation, training and job analysis as independent variable, and employee performance as dependent variable.The population of this research are all employees of PT. Warni Indah Cemerlang Pekanbaru which amounted to 35 respondents and all of them will be used as a sample of this research. Data analysis method in this research is multiple regression analysis.The result of using descriptive analysis is the motivation and training are not affect and positive to the performances of employees at PT. Warni Indah Cemerlang Pekanbaru. And the job analysis is affect and positive to the performances of employees at PT. Warni Indah Cemerlang Pekanbaru. This indicates that the three independent variables had a posotive effect on the dependent variable.Keywords : Motivation, Training, Job Analysis and Employee Performance